FEATURES OF THE DEVELOPMENT OF MENTAL CHANGES AT AWKWARD AGE (Scientific journal of the Fergana State University, 2023)
In this article, we attempt to consider how to understand and respond to the minds of adolescents associated with puberty and behavioral instability. The article uses research by Japanese scientists. According to the WHO definition, puberty is the period from the appearance of secondary sexual characteristics (the period of breast development, voice changes, etc.) to puberty (about 18–20 years).